Development and computational performance improvement of the wheel-rail coupling for heavy haul locomotive traction studies. Issue 1 (2nd January 2022) - Spiryagin, Maksym; Vollebregt, Edwin; Hayman, Mark; Persson, Ingemar; Wu, Qing; Bosomworth, Chris; Cole, Colin
Abstract : Locomotive-track interaction is a multidimensional task because it goes in many directions depending on the aim of the investigation. One such direction relates to wheel or track damage produced by traction and braking of locomotives under different train operational scenarios. The best option for performing wheel or track damage studies is to use the Exact theory developed by Kalker directly in the simulation procedure to solve the contact mechanics task at the wheel-rail interface. In this paper, a specially developed wheel-rail coupling is presented based on the Extended Contact library and incorporated in a full mechatronic model of a modern heavy haul locomotive. The implementation of the parallel computing technique in the locomotive model development allows for achieving reasonable computational performance. Thereby, this complex approach shows a perspective for competing with the standard approach that uses a sequential computing technique or combined study approaches, while at the same time providing accurate results that are required for locomotive/track damage studies.